A new species of Myrceugenia (Myrteae, Myrtaceae) from Distrito Federal, Brazil, with notes on its micromorphology - Gomes-Bezerra, Kadja Milena; Faria, Jair Eustáquio; Landrum, Leslie; Soares-Silva, Lucia Helena (Phytotaxa, 2014)
During field collections for the doctoral thesis of the first author, a population of Myrceugenia was found in a gallery forest along Bananal stream in the Distrito Federal, Brazil. This population was recognized as a new species related to Myrceugenia glaucescens and M. acutata, separated by 800 km or more from previously known populations of those species in Rio de Janeiro, Paraná, Santa Catarina and Rio Grande do Sul states.  Specimens were studied using scanning electron microscopy (SEM) and the leaf architeture was studied in diaphanized leaves.